Chitosan/Lignosulfonate Nanospheres as “Green” Biocide for Controlling the Microbiologically Influenced Corrosion of Carbon Steel - Pathath Abdul Rasheed (16846898) (2020)
In this work, uniform cross-linked chitosan/lignosulfonate (CS/LS) nanospheres with an average diameter of 150–200 nm have been successfully used as a novel, environmentally friendly biocide for the inhibition of mixed sulfate-reducing bacteria (SRB) culture, thereby controlling microbiologically influenced corrosion (MIC) on carbon steel. It was found that 500 µg·mL−1 of the CS/LS nanospheres can be used efficiently for the inhibition of SRB-induced corrosion up to a maximum of 85% indicated by a two fold increase of charge transfer resistance (Rct) on the carbon steel coupons. The hydrophilic surface of CS/LS can readily bind to the negatively charged bacterial surfaces and thereby leads to the inactivation or damage of bacterial cells. In addition, the film formation ability of chitosan on the coupon surface may have formed a protective layer to prevent the biofilm formation by hindering the initial bacterial attachment, thus leading to the reduction of corrosion. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma13112484